ANALYSIS OF THE RELATIONSHIP BETWEEN E-COMMERCE AND MSME DEVELOPMENT IN INDONESIA - Dara Ayu Adzani (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2022)
The purpose of this study was to determine the relationship between E-Commerce and Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. This is in line with the phenomenon of a significant increase in e-commerce in 2017-2021 which is considered to be able to encourage the development of MSMEs in Indonesia. This research uses quantitative research with simple linear regression analysis techniques and correlation analysis. The type of data used in this study uses time-series data (coherent) from 2011 to 2019 and data analysis that is processed using Eviews 12 software. The results of the analysis show that there is a very strong relationship between e-commerce and MSMEs. In addition, it is known that e-commerce transactions can affect the development of MSMEs in Indonesia. MSMEs are considered to contribute to Gross Domestic Product (GDP), and it is important for a country to encourage the increase of MSMEs